RESPONS PESERTA DIDIK TERHADAP PENERAPAN MODEL PEMBELAJARAN HYBRID LEARNING DI MTs NEGERI 2 SIDOARJO - Lailatul Hidayati; Rela Amalyaningsih; Astri Widya Ningrum; Umi Nurhayati; Nur Wakhidah (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
The Covid-19 pandemic has affected education and work systems around the world, causing schools and public places to be closed or limiting the number of users. Hybrid Learning is learning that combines two activities or learning models, namely combining online learning and face-to-face learning at the same time. Various kinds of perceptions of students who address the learning model. The focus of the study in this research is divided into three things, namely online learning, face-to-face learning, and hybrid learning. The purpose of this study was to determine how the perceptions of students at MTs Negeri 2 Sidoarjo on hybrid learning. This study uses descriptive quantitative methods with research instruments using interviews and an online questionnaire via Google Forms. Respondents in this study were students of MTs Negeri 2 Sidoarjo. The results of this study can be concluded that students like hybrid learning that is applied in schools. Because students prefer face-to-face learning because they can understand the material clearly and can interact directly with other students.